(untitled) (Journal of the College of Basic Education, 2022)
Talking about the other is talking about the self, as one cannot be separated from the other, whatever his rank, since God created Adam, may God bless him, created Eve with him, and man, whatever his condition, cannot live alone. The hadith of the pre-Islamic poet forms part of his discourse and his view of himself. It is not possible for the other to do any work, unless the self stands with him and stands beside him, for it is the secret of his existence and the level of his being. Without the self, the other cannot reach his goal, which is very difficult.The relationship between the self and the other is the thread that reproduces the creative thread, and if their dialectic often appears artificial in intellectual discourse, creativity provides it with the elements of construction and formulation, which expands the possibilities of its perception and expression.